Diaspora Networks as a Financial Catalyst: Navigating Global Markets for Kediri’s SMEs in the Netherlands and Australia - Pramana, Andy Chandra; Sudarmiatin; Pratikto, Heri (RISK : Jurnal Riset Bisnis dan Ekonomi, 2026)
This study analyzes how diaspora networks serve as financial catalysts for 47 Micro, Small, and Medium Enterprises (MSMEs) in Kediri, focusing on the culinary and creative industry sectors. The research explores combining domestic resources with global diaspora networks to mitigate financial constraints during internationalization. A qualitative approach with a multi-case study design was employed. Data was triangulated using semi-structured interviews, digital and field observations, and document studies , and was subsequently analyzed via Cross-Case Synthesis. The findings reveal that diaspora networks in the Netherlands and Australia act as crucial "financial bridges" utilizing bonding, bridging, and linking social capital. Specifically, the Dutch diaspora predominantly supports culinary MSMEs through bonding social capital to help meet European food standards , while the Australian diaspora aids creative industries through bridging social capital by acting as business intermediaries. Digital capabilities and FinTech integration significantly strengthen these connections, enabling real-time capital flow , reducing international transaction costs , and mitigating information asymmetry. In conclusion, diaspora networks provide "patient capital" that successfully lowers the cost of capital and diversifies funding sources for local enterprises. To ensure sustainable integration into global markets, MSMEs must prioritize advancing their digital capabilities and maintaining strict product standardization.